Addressing the Stigma Associated with Antiquated Blood Donation Policies and Donor Eligibility for MSM - Jay S. Picken; Helena R. Costakis (Georgia Southern University, 2022)
The crises of blood product shortages pose real health risks and threats to the greater population in the United States (U.S.). Current U.S. blood donation policies continue to restrict or limit donations from willing and healthy individuals on the basis of sex, classified as men who have sex with men (MSM). This essay explores the historical progression of the current blood donation policy through the lens of enacted stigmatization and stigma consciousness for MSM, identifies implications of the current policy, explores the impact of the current policy and proposed changes, and calls for action to modernize the current blood donation policies that create unwarranted discrimination. This paper focuses contextually on the national issue with a specific focus on the state of Georgia.